CONCEPTUAL APPROACHES TO DEFINING THE TERM “DIGITAL ECONOMY” - Petryshyn , Л.; Loboda , Н.; Zhydovska , Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The chosen topic of the research article involves highlighting modern interpretations of the content and features of the digital economy. This article presents and summarizes the results of the analysis of scientific approaches to defining the essence of the digital economy. The study has determined that the content of the elements of the digital economy can be disclosed based on the results of the digital transformation of economic activities of enterprises. The analysis of the substantiation of the conceptual apparatus carried out in the article made it possible to structure the conceptual approaches to the definition of the concept of “digital economy”. It is found that the key strategic documents on the development of the digital economy in Ukraine (Digital Agenda for Ukraine 2020, the Concept for the Development of the Digital Economy and Society of Ukraine for 2018–2020, and the Concept for the Development of Digital Competencies until 2025, Ukraine 2030E – a country with a developed digital economy) pay considerable attention to the specification of applied principles related to the development of the digital economy infrastructure and the development of digital competencies of citizens. It is established that many difficulties arise when assessing the scope of the digital economy precisely because there is no generally accepted definition of the digital economy and there is a lack of reliable statistical data on its components. It has been found that several initiatives are currently being implemented to remedy this state of affairs, but they are still not enough. In addition, there is a lack of adequate macroeconomic statistics that would allow an accurate assessment of the benefits of using digital products and those created based on digital technologies. It is found that today there are several synonyms for the digital economy: the Internet economy, the new economy, the web economy. All of these terms describe new trends in the development of economic and information relations and generally explain the type of economy where digital data are the main means of production.